The Effect of Topical Lidocaine Gel, Intrauterine Lidocaine Injection and Combination of these Two Methods for Relieving Pain during Curettage: A Double Blind Randomized Clinical Trial - Marzieh Beigom Khezri; Ezzatalsadat Haji Seyed Javadi; Farideh Movahed; Aida Zeinali; Ali Emami; Simin Dokht Molaverdikhani (Mashhad University of Medical Sciences, 2022)
Introduction: Curettage is one of the most common gynecological surgeries in women. Its complication is pain which increases dissatisfaction in patients. Therefore, it is necessary to find a way to treat this complication. This study was performed with aim to compare the effects of three methods of using lidocaine gel in the cervix, intrauterine injection of lidocaine, and a combination of two methods to reduce pain during curettage. Methods: This clinical trial study was performed in 2017 on 120 patients candidates for curettage in Qazvin Kosar Hospital. Patients were randomly divided into three groups of topical lidocaine gel in the cervix, intrauterine injection of lidocaine and a combination of these two methods, and the drugs were prescribed before curettage. Vital signs and pain were recorded in patients and other information was collected by completing the questionnaire. Data analysis was performed using statistical software (version 22) and chi-square and ANOVA tests. P<0.05 was considered statistically significant. Results: The intrauterine and intra cervical injection of lidocaine (0.3±0.72) and then injection of intra cervical lidocaine (0.45±0.84) alone significantly reduced pain during curettage in women (P=0.04). On the other hand, no severe hemodynamic changes were observed in these patients. No complications such as nausea and vomiting and no instability of vital signs were observed in any of the groups (P>0.05). Conclusion: Intrauterine administration along with addition of topical lidocaine gel to the cervix can be used as a simple, low-cost, and safe method as to control pain during and after curettage.